2019
DOI: 10.5232/ricyde2019.05505
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the movement assessment battery for children: a systematic review about gender differences. [Desempeño en la batería de evaluación del movimiento para niños: una revisión sistemática sobre las diferencias de género].

Abstract: A gender difference has been found in motor competence using several instruments. The Movement Assessment Battery for Children (MABC) seems to be one of the most developed instruments for children's motor coordination assessment, allowing the identification of developmental coordination disorders. Our study aimed to systematically review the differences in the motor performance between genders in studies using only the MABC. Five databases (Scopus, EBSCO+Sport Discus, Web of Knowledge, B-ON and Pubmed) were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Concerning children with DCD, Rodrigues et al [ 20 ] systematically analyzed the differences in motor performance between genders in studies that used only the MABC-2 [ 21 ]. Their results revealed that gender differences in performance were consistent across studies, since boys demonstrated more success and ease in activities involving gross motor skills, and girls performed better in the activities involving fine motor skills.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning children with DCD, Rodrigues et al [ 20 ] systematically analyzed the differences in motor performance between genders in studies that used only the MABC-2 [ 21 ]. Their results revealed that gender differences in performance were consistent across studies, since boys demonstrated more success and ease in activities involving gross motor skills, and girls performed better in the activities involving fine motor skills.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study found no gender differences in the MABC-2 assessment for both children with ASD and typically developing children, consistent with earlier findings by Henderson et al (2007) . A recent systematic review by Rodrigues et al (2019) on MABC-2 assessment in typically developing children indicated that approximately 75% of studies showed that boys outperformed girls in gross motor skills such as aiming and catching, while approximately 65% of studies found that girls outperformed boys in fine motor skills such as manual dexterity, with no consensus reached regarding balance skills (static and dynamic balance). However, due to the exclusion of certain age groups (3–16 years) in some studies or the utilization of different versions of the MABC, gender differences may have been underestimated or overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The superior ability of women to perform fine tasks of motor coordination (Rodrigues, Ribeiro, Sousa, Lopes, & Barros, 2019) could be presented as a possible explanation to the better response in the variable vigor in women. Better coordination could help to facilitate the actions to be taken during the rhythm therapy session, which could explain the higher satisfaction levels among women.…”
Section: Discussionmentioning
confidence: 99%